A case of Phoma fungal keratitis in a contact lens user. (18th March 2015) - Kumar, Periyasamy; Thomas, Shery; Papagiannuli, Efrosini; Hardman, Susan C; Jenkins, David; Prydal, Jeremy
Lesson: Fungi of the genus Phoma are common plant pathogens and saprophytes and are rarely pathogenic to animals.